Broad-band X-ray analysis of local mid-infrared-selected Compton-thick AGN candidates. Issue 2 (17th May 2019) - La Caria, M-M; Vignali, C; Lanzuisi, G; Gruppioni, C; Pozzi, F
ABSTRACT: The estimate of the number and space density of obscured active galactic nuclei (AGNs) over cosmic time still represents an open issue. While the obscured AGN population is a key ingredient of the X-ray background synthesis models and is needed to reproduce its shape, a complete census of obscured AGN is still missing. Here we test the selection of obscured sources among the local 12 μ m sample of Seyfert galaxies. Our selection is based on a difference of up to three orders of magnitude in the ratio between the AGN bolometric luminosity, derived from the spectral energy distribution (SED) decomposition, and the same quantity obtained by the published XMM–Newton 2–10 keV luminosity [L_ bol^ AGN(IR)/L_ bol^ AGN(X) ]. The selected sources are UGC05101, NGC 1194, and NGC 3079 for which the available X-ray wide bandpass, from the Chandra and XMM–Newton plus NuSTAR data, extending to energies up to ∼30–45 keV, allows us an accurate determination of the column density, and hence of the true intrinsic power. The newly derived N H values clearly indicate heavy obscuration (∼1.2, 2.1, and 2.4 × 10 24 cm −2 for UGC05101, NGC 1194, and NGC 3079, respectively), and are consistent with the prominent silicate absorption feature observed in the Spitzer -IRS spectra of these sources (9.7 μ m rest frame). We finally checked that the resulting X-ray luminosities in the 2–10 keV band are in good agreement with those derived from the mid-IR band through empirical L MIR – L X relations.